PENGARUH PEMBIAYAAN MURABAHAH, MUSYARAKAH DAN MUDHARABAH TERHADAP PROFITABILITAS PADA PT BANK PANIN DUBAI SYARIAH Tbk - A.Tarmizi; Nurlia Fusfita; Abdul Rahman Sidik (Jurnal Publikasi Manajemen Informatika, 2023)
This study aims to determine and analyze the effect of mudharabah, musyarakah and murabahah financing on the profitability of Bank Panin Dubai Syariah Tbk period 2014-2021. This study uses a quantitative approach and the data analysis method used is multiple linear regression analysis with a significance level of 5%, the sample is used in this study as many as 32 data samples taken from the quarterly report of Panin Dubai Syariah Bank. The results showed that partially, mudharabah and murabahah had no effect on profitability and musharaka had no effect on profitability. Simultaneously shows that the variables mudharabah, musyarakah and murabahah have an effect on profitability at Bank Panin Dubai Syariah Tbk period 2014-2021. The results of the calculation of the coefficient of determination show that the financing of mudharabah, musyarakah and murabahah on profitability has an effect of 50.2% and the remaining 49.8% is influenced by other variables outside of this study.